Space and art – interrelations between architecture and contemporary art at Inhotim - Valente, Liz Fagundes Oliveira (2016)
This thesis is the result of a phenomenological research study, where the object of the research is the interrelations between architecture and contemporary artistic expressions at Inhotim. The theory of phenomenology acknowledges that the sensory experience of space is also unique function of space. In architecture it is demonstrated through the manipulation of material and immaterial elements of space in order to produce an impact on the human senses. Since the consolidation of contemporary art, particularly post-object1 art such as environment, site-specific, new media, installations and others that convey sensorial experiences, the need to preserve the relationship between the work and its place has strengthened. Changes in what/how art is have interfered in how art spaces are. Therefore, through the case of the Inhotim, the central matter that this thesis seeks to address is how the changes of paradigms in the arts brought about new architectural conformations that better accommodate contemporary art. This work is organized in three scales of analysis of this interrelation: (1) the scale of the artistic fact in relation to space; (2) the scale of the gallery in relation to the artistic fact; and, (3) the scale of the whole physical space of the museum, approaching Inhotim as whole, reading into its path- oriented form, its created landscapes and architectural set. The term “post-object” was extracted from CARRIER, D. The art museum today. Curator: The museum journal. Volume 54, Issue 2, pages 181–189, April 2011.